Term Back / Detention Policy Revision Measures in Academic Medical and Allied Institutions of Pakistan in the COVID-19 Epidemic for the Session 2019-2020 - Irshad Hussain; Ehsanuullah Malik; Muhammad Shahzad Raza (Journal of Rawalpindi Medical College, 2020)
The Pakistan Medical and Dental Council (PM&DC) is the body concerned for the medical and dental education in Pakistan.1 The council was dissolved by an order of the President of Pakistan in October 2019, 2 but the order was revoked by the decision of the High Court of Pakistan.3 According to the PM&DC return/detention policy, a medical student has two chances of exam for his promotion in the next academic class and if one of the students could not pass the two chances provided in at least one of his subjects, the student must pass the exam in 3rd attempt with loss of his / her academic year and must pursue medical studies with the junior class. If one of these students could not pass this or these subjects by exceeding the 3rd chance, the conceded institution offers the 4th and last opportunity to the student.1 If the student still cannot pass the subject in 4th and last opportunity, he is expelled from the establishment with the cancellation of his admission, and the dreams of such a student to become a doctor are fulfilled until he will only be readmitted upon reappearing in the PM&DC competitive entrance test. But due to the sudden and unexpected outbreak of Covid-19, the medical community was the most affected. In some countries, more death rates have been reported among physicians who performed Covid-19 patient care tasks.4 Due to the lockdown policy of Govt. of Pakistan across the country, academic medical institutions were closed as a result of academic months of medical and dental students have also been wasted like other academic fields. The lockdown has been continued and we expect further academic waste from these students. The Pakistan Higher Education Commission has asked for conducting online courses for these students, but the clinical subjects of medical students cannot be taught online as they require direct clinical exposure to patients for the transmission of learning. required. Therefore, as a result of Covid-19, there is expected to be a waste of courses from almost all students across the country. However, in such circumstances, detained / term-back students will suffer a greater and irreparable waste of time as there may be many other technical difficulties regarding the continuation of medical education and the examinations of these students due to the Covid-19 disaster. Therefore, it may be good to revise the Term-Back / Detain policy for these medical, dental, and related students. The authors made the following suggestions for the PM&DC and the institutions to consider this review.